2021
DOI: 10.3390/brainsci11020209
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Human Pluripotent Stem-Cell-Derived Astrocyte Model with Forebrain Identity

Abstract: Astrocytes form functionally and morphologically distinct populations of cells with brain-region-specific properties. Human pluripotent stem cells (hPSCs) offer possibilities to generate astroglia for studies investigating mechanisms governing the emergence of astrocytic diversity. We established a method to generate human astrocytes from hPSCs with forebrain patterning and final specification with ciliary neurotrophic factor (CNTF). Transcriptome profiling and gene enrichment analysis monitored the sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Human pluripotent stem cells (hPSCs) were maintained on Matrigel-coated plates in Essential 8 medium (E8; Thermo Fisher Scientific Ltd., Vantaa, Finland). Astrocytes were differentiated as previously described (Peteri et al, 2020). Briefly, for differentiation, 80% confluent hPSCs were dissociated with 0.5 mM ethylene-…”
Section: Generation Of Human Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human pluripotent stem cells (hPSCs) were maintained on Matrigel-coated plates in Essential 8 medium (E8; Thermo Fisher Scientific Ltd., Vantaa, Finland). Astrocytes were differentiated as previously described (Peteri et al, 2020). Briefly, for differentiation, 80% confluent hPSCs were dissociated with 0.5 mM ethylene-…”
Section: Generation Of Human Astrocytesmentioning
confidence: 99%
“…We used hPSC-derived forebrain astrocyte model (hASTRO) meaning astrocytes at D95 of differentiation in vitro (Peteri et al, 2020) to study putative alterations of human FXS astrocytes (Figure 1a). Differentiation of astrocytes followed the developmental processes of astrocytes from neuroepithelial induction and regional patterning using morphogens to progenitor expansion and astrocyte specification/maturation (Russ et al, 2021).…”
Section: Differentiation Of Astrocytes Modeling Fxsmentioning
confidence: 99%
“…However, significant differences were reported between human and mouse astrocytes, including larger size, increased morphological complexity as well as differing subtypes defined by their expression profiles amongst other techniques (Oberheim et al, 2009 ; Ji et al, 2019 ; Escartin et al, 2021 ). One way to address the role of DOR in human astrocytes would be the use of human astrocytes derived from induced pluripotent stem cells (iPSC) in vitro , although in vitro culture induces astrocytes that differ from in vivo astrocytes (Barbar et al, 2020 ; Franklin et al, 2021 ; Peteri et al, 2021 ). Of note, human iPSC-derived astrocytes could be grafted into the mouse brain and retain human-specific features (Preman et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have explored hiPSC-derived glial cells in the study of FXS. One group recently published a method to generate astrocytes with forebrain patterning from hPSCs (hASTRO) [ 144 ]. Using this method, the group found that the expression of urokinase plasminogen activator (uPA), a protease that regulates the degradation of the extracellular matrix, was increased in FXS hASTRO compared to control hASTRO [ 145 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%